Integration of virtual and on-line machining process control and monitoring. Issue 1 (2017) - Altintas, Y.; Aslan, D.
Abstract: This paper presents a virtually assisted on-line milling process control and monitoring system. A part machining process is simulated to predict the cutting forces, torque, power, chip load and other process states. The simulated machining states are accessed by a real time monitoring system which detects the tool failure and adaptively adjusts the feed by predicting the forces from the feed and spindle drive motor current supplied by CNC. The integration of virtual simulation with real time measurements avoids false tool failure detection and transient overloads of the tools during adaptive control. The system has been implemented on a CNC machining centre for use in production.